THE IMPACT OF SOCIAL MEDIA ON RECRUITMENT IN KINGDOM OF SAUDI ARABIA - Ayah Waleed Gashgari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Social media have become increasingly popular in recent years. The use of social media is becoming a major hit for both personal and professional use. Many companies in the Kingdom of Saudi Arabia (KSA) are using social media such as Facebook, Twitter and LinkedIn to advertise their jobs so that job seekers can apply for a job. Companies using social media for recruitment may have a good or bad effect on recruitment process. Therefore, this study was done to analyze the impact of social media usage for recruitment purpose. This work was done based on quantitative method. The sample population consisted of 38 human resource managers from various companies in Saudi Arabia. Questionnaire was utilized for data collection. The findings of this work have shown that companies in KSA are using the social media for recruitment purpose. Furthermore, the results have shown that HR social media is an effective tool in finding job vacancies. Moreover, results have shown that companies in KSA are having policies while using social media to recruit employees. HR managers stated that social media helps in managing the recruitment process.